Optimization of a Truss Structure Used to Design of the Manipulator Arm from a Set of Components - Jaroslav Rojíček (MDPI AG, 2021)
The design of a manipulator arm, which is built from a construction kit, is presented in this article. The procedure is based on the results of the discrete optimization of a truss structure and its application to a simple component system (assuming a predefined shape and material of components). A genetic algorithm is used to optimize the truss structure, and the results of the solution are verified on a simple task used in literature (the code was written in the Python language). The construction kit was inspired by Merkur®, and the article proposes several components with different shapes and materials. The construction kit and the optimization of the truss structure were used to design the manipulator arm. The truss topology has been predefined with respect to the construction set. The finite element method (software ANSYS®) was used to analyze the components (shell elements) and truss structures (linear analysis, buckling analysis, etc.). To validate the presented approach, the arm designed by topological optimization was used. The comparison shows that the use of components may be an alternative to topology optimization and additive manufacturing. The next step will be the modification of the presented method in order to minimize the differences between the simplified task used for optimization (truss structure-rod element) and the simulation composed of components (components assembly-shell element).